Chest tightness variant asthma: deja vu all over again - Zhong, Nanshan (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
Asthma is a serious problem that, according to WHO estimates, affects 235 million people (1). Apart from the typical symptoms of "recurrent episodes of wheezing, dyspnea, chest tightness, and coughing, particularly at night or in the early morning" (2), asthma may be manifested in various clinical phenotypes, and readily misdiagnosed as conditions such as chronic bronchitis, cardiovascular diseases, and mental disorders. Raising physicians' awareness of these clinical phenotypes can be of significant help in reducing misdiagnosis of asthma.